Semantic web and web science - Qi, Guilin; Zhao, Dongyan; Nejdl, Wolfgang; Zheng, Hai-Tao; Li, Juanzi (Springer Proceedings in Complexity, 2013)
Semantic Web and Web Science focuses on exploring state of the art research in semantic web and web science. The rapidly evolving World Wide Web has led to revolutionary changes in the whole of society. The research and development of the semantic web covers a number of global standards of the web and cutting edge technologies, such as: linked data, social semantic web, semantic web search, smart data integration, semantic web mining and web scale computing.  These proceedings are from the Sixth Chinese Semantic Web Symposium.